Bourdieu and the "pessimism of reason" - Miguel, Luis Felipe (Tempo Social, 2015)
One of the recurring criticisms of Pierre Bourdieu's sociology is its emphasis on the mechanisms through which social structures are reproduced, rather than their transformation. This criticism first appears in the sociology of education, marked by the impact of his book with Jean-Claude Passeron, entitled precisely La reproduction. It also echoes in other areas where Bourdieu's theory of fields is applied, though, such as politics. It is through politics that I intend to show how, in his major works, Bourdieu provides us with a worldview that is highly realistic in terms of the strength of the mechanisms of reproduction and that, without being disillusioned about processes of change, reveals that these are more complex and nuanced by elements of maintenance than transformative utopias would have us believe.